2022
DOI: 10.1186/s12917-022-03338-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiological study of germline APC variant associated with hereditary gastrointestinal polyposis in dogs: current frequency in Jack Russell Terriers in Japan and breed distribution

Abstract: Background Cases of gastrointestinal (GI) neoplastic polyps in Jack Russell Terriers (JRTs) have increased in Japan since the late 2000s. We recently demonstrated that JRTs with GI polyps heterozygously harbor an identical germline variant in the adenomatous polyposis coli (APC) gene, c.[462_463delinsTT]; therefore, this is an autosomal dominant hereditary disease. We conducted a molecular epidemiological study to explore the current frequency of the APC variant in JRTs in Japan and the breed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 18 publications
0
17
0
2
Order By: Relevance
“…According to data compiled by the Japan Kennel Club (JKC) [ 8 ], JRTs have maintained a certain level of popularity in Japan over the last two decades, and nearly 3500 JRTs were registered in the JKC in 2021, ranking 16th among all purebred dogs. In our prior epidemiological survey conducted in 2020, the frequency of germline APC variants in Japan was determined to be 1.89% in a screening of approximately 800 JRTs [ 10 ]. Taken together, a certain number of JRTs with germline APC variants are still present today in Japan, and veterinary clinicians and pathologists would have the opportunity to examine patients and their GI lesions for some time in the future.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to data compiled by the Japan Kennel Club (JKC) [ 8 ], JRTs have maintained a certain level of popularity in Japan over the last two decades, and nearly 3500 JRTs were registered in the JKC in 2021, ranking 16th among all purebred dogs. In our prior epidemiological survey conducted in 2020, the frequency of germline APC variants in Japan was determined to be 1.89% in a screening of approximately 800 JRTs [ 10 ]. Taken together, a certain number of JRTs with germline APC variants are still present today in Japan, and veterinary clinicians and pathologists would have the opportunity to examine patients and their GI lesions for some time in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, a certain number of JRTs with germline APC variants are still present today in Japan, and veterinary clinicians and pathologists would have the opportunity to examine patients and their GI lesions for some time in the future. Moreover, judging from the fact that there were many JRTs introduced from overseas in the ancestors of the JRTs with the APC variant found in Japan [ 10 ] and that JRTs are also popular breeds outside Japan, it is likely that veterinarians in other countries could encounter JRTs with hereditary GI polyposis. It has previously been reported that JRTs with hereditary GI cancers have a significantly longer survival time than sporadic cases but were at a higher risk for disease recurrence [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations